PEMBELAJARAN BERMAKNA BERBASIS DARING DI TENGAH PANDEMI COVID-19 - Ilham Baharuddin (Kelola: Journal of Islamic Education Management, 2020)
The Covid-19 pandemic forced the ministry of education to adopt a policy of "learning from home" according to government regulations to prevent and break the spread. One of the problems is students are not ready with the culture of learning outside the classroom using online media. In addition, teachers are still confused in deciding the methods used in online learning. From various literatures, meaningful learning models are very effective to use in the current conditions. This research uses library research method by taking analysis data from various references. The purpose of this study is to describe a meaningful learning model using online media. From the reading results it was found that there were six points in conducting the learning process with meaningful learning models namely determining learning objectives, identifying student characteristics, selecting subject matter, determining information in accordance with meaningful learning, learning the core concepts, and evaluating student learning processes and outcomes.